External stakeholders’ pressure on environmental accounting reporting in SMEs in Shanxi Province, China - Sulaiman Tahajuddin; Zhao, Xin; Abdul Wahid Mohd Kassim (International Journal of Multidisciplinary Research and Publications, 2020)
This paper investigates the effect of the pressure from external stakeholders on Environmental accounting reporting (EAR) in SMEs in Shanxi Province, China. A total of 88 respondence was collected in this study. The data were analyzed by utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 3.3.2. The empirical results showed that the customers in SMEs in Shanxi province, china were able to pressure the companies to implement environmental accounting reporting. The study also found that, suppliers’ pressure do not have influence on environmental accounting reporting. The results of this study prove that customers think about environmental issues, because environmental accounting reports can improve the profits of SMEs in terms of environment, cost, high-efficiency technology, and lowpollution, non-pollution products, so that customers can buy cheaper and better quality products